Telemedicine for infectious disease care—how do we measure the true value? - Palacholla, Ramya Sita; Kvedar, Joseph C. (Annals of Translational Medicine, 2019)
Telemedicine technologies are increasingly being used to deliver healthcare services because of their potential to eliminate distance barriers and improve access to care. Additionally, telemedicine has led to the improved clinical outcomes and cost-savings as demonstrated by multiple studies in different disease populations (1-4). Findings from these studies include reduction in hospitalizations and use of other acute healthcare services, as well as improvement in the quality of life, clinical outcomes and patient satisfaction particularly in patients with chronic diseases (1-4).